1990
DOI: 10.1159/000107132
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Morphometric Analysis of Basal Forebrain Neurons Expressing β-Nerve Growth Factor Receptors in Normal and Alzheimer's Disease Brains

Abstract: The number and size distribution of β-nerve growth factor (p-NGF) receptor-immunoreactive neurons has been examined in the nucleus of the diagonal band and the anterior, intermediate and posterior regions of the nucleus basalis of Meynert in Alzheimer''s disease (AD) and compared with normal brain. The number of neurons was in general lower in AD, although there was not a statistically significant reduction in any region of the basal nuclei. In some regions, there was an increase in the proportion of small neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…This loss probably reflects the loss of cholinergic neurons in this structure [1][2][3] since we have shown that these receptors are mainly expressed by cholinergic neu rons [19]. This is in agreement with the presence of NGF receptors on cholinergic neurons previously reported in this structure [15,17,22], Nevertheless, whether this loss is the event that leads to neurodegeneration remains to be determined.…”
Section: Trka-like Immunoreactivity In the Basal Forebrain O F Patiensupporting
confidence: 87%
See 1 more Smart Citation
“…This loss probably reflects the loss of cholinergic neurons in this structure [1][2][3] since we have shown that these receptors are mainly expressed by cholinergic neu rons [19]. This is in agreement with the presence of NGF receptors on cholinergic neurons previously reported in this structure [15,17,22], Nevertheless, whether this loss is the event that leads to neurodegeneration remains to be determined.…”
Section: Trka-like Immunoreactivity In the Basal Forebrain O F Patiensupporting
confidence: 87%
“…In the rat [14] and in humans [15][16][17], low-affinity receptors have been described on cholinergic neurons of the nucleus basalis of Meynert, but not in the striatum or pedunculopontine nucleus. Autoradiographic studies, in the rat [14] and in humans [18], have demonstrated the presence of high-affinity l23I-NGF-binding sites (presum ably corresponding to TrkA) in the nucleus basalis of Meynert and the striatum, and their absence in the pedun culopontine nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…One study reported a substantial reduction of p75 NTR -immunoreactivity (cell area and fibre staining) in neurons of the nbM [61]. This differs from an earlier study [59] examining number and size of p75-immunoreactive ne- Both cell body and fibres are stained. The staining has a punctuate appearance and can be seen at the cell surface and also in the perinuclear region.…”
Section: Cholinergic Function and The Basal Forebrainmentioning
confidence: 68%
“…Assessment of the numbers of basal forebrain cholinergic cell bodies has revealed a wide range of loss, with largest reductions seen in early onset patients [59][60][61]. One study reported a substantial reduction of p75 NTR -immunoreactivity (cell area and fibre staining) in neurons of the nbM [61].…”
Section: Cholinergic Function and The Basal Forebrainmentioning
confidence: 99%
“…3 B-D (2,17,29). Interestingly, morphometric and immunohistochemical studies of the AD basal forebrain using antibodies to ChAT and nerve growth factor receptor have documented shrinkage of immunoreactive cell bodies (26,27). By using ChAT immunocytochemistry, a 25% decrease was found (26).…”
mentioning
confidence: 99%